Deep Sequencing Reveals Central Nervous System Compartmentalization in Multiple Transmitted/Founder Virus Acute HIV-1 Infection - Sodsai Tovanabutra; Rujipas Sirijatuphat; Phuc T. Pham; Lydia Bonar; Elizabeth A. Harbolick; Meera Bose; Hongshuo Song; David Chang; Celina Oropeza; Anne Marie O’Sullivan; Joyce Balinang; Eugene Kroon; et al. (Cells, 2019)
HIV-1 disseminates to a broad range of tissue compartments during acute HIV-1 infection (AHI). The central nervous system (CNS) can serve as an early and persistent site of viral replication, which poses a potential challenge for HIV-1 remission strategies that target the HIV reservoir. CNS compartmentalization is a key feature of HIV-1 neuropathogenesis. Thus far, the timing of how early CNS compartmentalization develops after infection is unknown. We examined whether HIV-1 transmitted/founder (T/F) viruses differ between CNS and blood during AHI using single-genome sequencing of envelope gene and further examined subregions in pol and env using next-generation sequencing in paired plasma and cerebrospinal fluid (CSF) from 18 individuals. Different proportions of mostly minor variants were found in six of the eight multiple T/F-infected individuals, indicating enrichment of some variants in CSF that may lead to significant compartmentalization in the later stages of infection. This study provides evidence for the first time that HIV-1 compartmentalization in the CNS can occur within days of HIV-1 exposure in multiple T/F infections. Further understanding of factors that determine enrichment of T/F variants in the CNS, as well as potential long-term implications of these findings for persistence of HIV-1 reservoirs and neurological impairment in HIV, is needed.